α-Amylase and α-Glucosidase inhibitory activity assessment of Cucurbita maxima seeds – a LIBS based study - Devesh Kumar Kushawaha; Manjulika Yadav; Sanjukta Chatterji; Amrita Kumari Srivastava; Geeta Watal (International Journal of Phytomedicine, 2016)
The aim of the present study was to investigate, α-amylase and α-glucosidase inhibitory activities of the aqueous extract of Cucurbita maxima seeds in vitro and to correlate their activity with their phytoelemental profile quantitatively assessed by Laser-Induced Breakdown Spectroscopy (LIBS). Diabetes can be managed by controlling postprandial hyperglycemia which can be achieved by inhibiting carbohydrate hydrolyzing enzymes like α-amylase and α-glucosidase. Results reveal that the C. maxima seeds have appreciable α-amylase inhibitory activity of 46.03±1.37% with IC50 value at 7.00±0.29 mg ml-1 in addition to substantial α-glucosidase inhibitory effect of 35.11±1.04% with IC50 at 8.11±0.36 mg ml-1. Acarbose was used as a reference. LIBS analysis showed the presence of certain phytoelements viz. Mg, Ca, K and Na which are well known glycemic elements and hence could be responsible for inhibitory activity of carbohydrate hydrolyzing enzymes.Thus, α-amylase and α-glucosidase inhibitory action of C. maxima seeds would be responsible for their antidiabetic activity. The glycemic elemental profile further validates their role in controlling diabetes and hence C. maxima seeds could be explored as a potential herbal candidate for managing postprandial hyperglycemia causing type 2 diabetes mellitus.